Effects of substrate thermal properties on the heat transfer coefficient of vapour phase soldering. (October 2016) - Illés, Balázs; Géczy, Attila; Skwarek, Agata; Busek, David
Highlights: Study of heat transfer coefficient during VPS process by numerical simulations. 3D model was used to describe the phase change and the transfer mechanisms. Dynamic HTCs of the VPS process were presented for different substrate materials. HTC is defined by substrate thermal diffusivity and the condensate layer thickness. Condensate layer forming is determined by volumetric heat capacity of the substrate. Abstract: In this paper, dependence of heat transfer coefficient during vapour phase soldering on the substrate properties was investigated by numerical simulations. A three-dimensional model was developed to describe the phase change on the substrate and the transfer mechanisms in the condensate layer. Five different substrate materials were studied: FR4, polyimide, 94% alumina, LTCC glass–ceramic and insulated metal substrate. The effect of the substrate aspect ratio was also studied. The results present dynamic heat transfer coefficient values of the process for different substrate materials. It is shown that during vapour phase soldering – which is a transient-state condensation process – the heat transfer coefficient can be characterized with the thermal diffusivity of the substrate material together with the filmwise condensate layer thickness on the substrate. The formation of the condensate layer is determined by the thermal diffusivity of the substrate material. It was also found that the aspect ratio of the substrates influences the movement of the condensate on the surface of the substrate, ultimately leading to a substantial effect on the heat transfer coefficient.